2017
DOI: 10.1371/journal.pone.0187582
|View full text |Cite
|
Sign up to set email alerts
|

The influence of computer-based cognitive flexibility training on subjective cognitive well-being after stroke: A multi-center randomized controlled trial

Abstract: BackgroundStroke can result in cognitive complaints that can have a large impact on quality of life long after its occurrence. A number of computer-based training programs have been developed with the aim to improve cognitive functioning. Most studies investigating their efficacy used only objective outcome measures, whereas a reduction of subjective cognitive complaints may be equally important for improving quality of life. A few studies used subjective outcome measures but were inconclusive, partly due to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
(74 reference statements)
0
18
0
1
Order By: Relevance
“…Items included bathing, dressing, eating, transferring, indoor walking, and toileting. On the other hand, the Lawton-Brody Instrumental Activities of Daily Living Scale 8 is a popular assessment of IADLs, which has been validated in a previous study 47 , and multiple studies involving this measurement have been published in older adults 48 , patients with stroke 49 , and those with cognitive impairment 50 . The current study used a nine-item modified version of the original eight items, with housework subdivided into light and heavy housework, and additionally including transport, managing finances, shopping, laundry, medication, food preparation, and using the telephone.…”
Section: Methodsmentioning
confidence: 99%
“…Items included bathing, dressing, eating, transferring, indoor walking, and toileting. On the other hand, the Lawton-Brody Instrumental Activities of Daily Living Scale 8 is a popular assessment of IADLs, which has been validated in a previous study 47 , and multiple studies involving this measurement have been published in older adults 48 , patients with stroke 49 , and those with cognitive impairment 50 . The current study used a nine-item modified version of the original eight items, with housework subdivided into light and heavy housework, and additionally including transport, managing finances, shopping, laundry, medication, food preparation, and using the telephone.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers indicated the need for an appropriate practise duration for the training to be more effective, since a short-termed cognitive training usually renders only a brief and temporary effect [10, 12]. However, van de Ven et al indicated that the connection between the duration of training and the effectiveness of the impact remained unclear [30]. The interactive experience should be perceived by the OT specialist as well as by the patient as a very positive factor allowing continued treatment without fatigue or boredom [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various types of complaints may have different meaning for the development of predictive subtypes of MCI or dementia (Gu, Fischer, Saposnik, & Schweizer, 2013). Regarding the importance of data in clinical practice, it has been shown that cognitive function training reduces the severity of SCD in healthy older adults (Kwok, Bai, Li, Ho, & Lee, 2013), especially in adults with SCD (López-Higes et al, 2018) and after stroke (van de Ven et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Referring to the discussions outlined in the introduction, whether the SCD can be considered as an indicator of actual cognitive difficulties or depressive mood, we have reason to indicate two mechanisms of SCD -emotional and/or cognitive. Stimulation of cognitive functions and/or prevention of depression (treatment) are effective in reducing complaints in people without dementia (Kwok et al, 2013;López-Higes et al, 2018;van de Ven et al, 2017). However, these techniques may not be effective when complaints are part of developing dementia.…”
Section: Discussionmentioning
confidence: 99%